Optimalisasi Pelatihan Masyarakat dalam Pengelolaan Homestay di Sekitar Candi Tebing Tegallinggah - Ni Putu Helda Silpia Apriyani; Ida Ayu Ketut Ratna Dewi; Jeanny Pricilia Anneke W; I Wayan Erik Susanto (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
Community training and mentoring in managing homestays around Tebing Tegallinggah Temple aims to improve the capacity of local communities in providing quality accommodation that can meet tourist expectations and support the development of community-based tourism in the area. By identifying the lack of accommodation options close to the site, this program seeks to address accessibility issues and increase the attractiveness of Tebing Tegallinggah Temple as a cultural tourism destination. The research method used is a qualitative approach with primary data collection through observation, interviews, and documentation, as well as secondary data from literature and related reports. The analysis was carried out qualitatively descriptively and supported by Focus Group Discussions (FGD) to obtain a comprehensive picture from various stakeholders. The results of this activity indicate that the training provided has succeeded in improving the knowledge and skills of the working community in managing homestays collaboratively. With the presence of well-managed homestays, tourists now have alternative accommodation that is closer to Tebing Tegallinggah Temple, reducing dependence on hotels in Ubud and increasing the comfort of visiting. In addition, the development of homestays also contributes to improving the economic welfare of local communities through new business opportunities in the tourism sector. This program also emphasizes the importance of effective and integrated promotion with various tourism stakeholders to maximize the potential of the destination. Overall, these results underline the relevance and urgency of the program in supporting sustainable and inclusive tourism development around Tebing Tegallinggah Temple.